TECHNOLOGY USE IN LEARNING TO READ: A LITERATURE REVIEW - Otang Kurniaman; L.N. Firdaus; Hadriana; Sumarno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Learning to read in the 4.0 revolution era should be more focused on learning in the use of technology. Hence, the purpose of the research in this article was to analyze the learning process based on methods, analytical techniques, and findings in the terms of applying reading learning technology findings and analyzing the findings of publications on Google Scholar and Scopus. The type of research was literature research using a systematic review, which provided an overview of the publication of articles with the number of found data 56 articles. After conducting the review process, it was obtained that 25 articles matched the criteria. The research results showed that the most publications on the use of technology were in 2014, 2019, and 2021. Related to the place of publication, most publications used Scopus and Sinta 3 as many as 6 articles. The use of research was based on the research methods, which were mostly used on development methods at 48%. Thus, it could be seen from the results of the research that the use of technology in learning to read is able to improve reading skills.